Studi dan Implementasi Pengenalan Wajah dengan Menggunakan Pencocokan String Boyer Moore - Suharto Siregar (Bulletin of Computer Science Research, 2020)
Image processing is a system where the process is carried out with the input in the form of an image and the result is also an image. Initially, image processing was carried out to improve image quality, but with the development of the world of technology, which was marked by the increasing capacity and speed of computer processing, as well as the emergence of computational science that allowed humans to retrieve information from an image, image processing could not be separated from it. In this research, image processing is applied to face recognition using moore boyer string matching. Boyer Moore is a technique in image processing that functions to match strings. The problem of facial recognition is how to search for strings on faces based on Boyer Moore's strings by matching the strings. Therefore, it is very important research that aims so that computers can have the function of detecting faces. If computers can be designed to have intelligence closer to that of humans, of course this can facilitate human work.